Analisis Pemanenan Air Hujan Dengan Memanfaatkan Atap Dalam Memenuhi Kebutuhan Air Bersih - Ukmin Raru, Suparman Ajis; Mawardin, Adi (Indonesian Society of Applied Science, 2024)
The need for water is increasing due to the increasing human population while water sources. This can result in a lack of clean water for humans themselves. Optimizing the use of water and water catchment areas needs to be done to preserve water. Location in the settlement area of Padak Hamlet, Labuan Sumbawa Village, Sumbawa Subdistrict, Sumbawa Regency. The area is located in a coastal area which has a very high probability of soil quality so that sea water is very easy to enter until the well water tastes salty. The use of PDAM water also experiences water difficulties in terms of flowing because there are several places where the elevation tends to be higher so that PDAM water is very difficult to push, so the community decided not to use PDAM water since the last seven years, so by collecting rainwater it is expected to meet the needs of clean water. The purpose of the research is to find out how much rainwater harvesting potential through roof media and find out how much water needs for household scale with random sampling method and calculate the roof area, as well as the average of rainfall from 2914-2023. It resulted in a total roof area of 3118,365 m2 with an average rainfall of 12,900 mm/year. The average rainfall with a 99% chance of occurring was 15.99 mm/month, the average water availability was 235.824 m3/month, with an average water demand of 125 m3/month.